377 Sentinel lymph node detection in endometrial cancer: laparoscopic versus robotic approach. (13th November 2020) - Bizzarri, N; Restaino, S; Gueli Alletti, S; Monterossi, G; Gioè, A; La Fera, E; Gallotta, V; Fagotti, A; Scambia, G; Fanfani, F
Abstract : Introduction: Sentinel lymph node (SLN) mapping with indocyanine green (ICG) is widely utilized in the staging process for apparent uterine-confined endometrial cancer. The aims of the present study were to assess bilateral SLN mapping with laparoscopic versus robotic approach, to assess variables affecting bilateral detection rate and to assess survival difference in patients with no/unilateral, compared to bilateral SLN detection. Methods: All patients diagnosed with endometrial cancer FIGO stage IA-IVB, treated with minimally-invasive primary surgery and undergoing indocyanine-green (ICG) injection to detect SLN, between 01/2015–12/2019, were included. Results: 387 (70.5%) patients had bilateral SLN mapping, 102 (18.6%) and 60 (10.9%) had unilateral and no mapping, respectively. Patients who underwent robotic approach were older (median 61 versus 64 years, p=0.046) and had a higher BMI (median 26.0 versus 34.8 kg/m2, p<0.001). No difference in any SLN mapping or in bilateral SLN detection was evident between laparoscopic or robotic approach (p=0.892 and p=0.507, respectively). Patients with bilateral SLN detection in the entire cohort were younger (p<0.001) and had better 3-year DFS compared to patients with no/unilateral SLN mapping (77.0% versus 66.3%, respectively, p=0.036). No 3-year OS difference was reported (p=0.491). Conclusions: SLN mapping and bilateral SLN detection with ICG in endometrial cancer was not different in laparoscopic and robotic approach, even though patients undergoing robotic approach were older and more obese. Bilateral SLN detection was associated with improved 3-year DFS, but not with 3-year OS, compared to no and unilateral SLN detection.